2008
DOI: 10.1002/ijc.23384
|View full text |Cite
|
Sign up to set email alerts
|

Elevated risk for squamous cell carcinoma of the conjunctiva among adults with AIDS in the United States

Abstract: Squamous cell carcinoma of the conjunctiva (SCCC) has been associated with HIV infection in equatorial Africa, but the evidence for association with HIV in developed countries, where SCCC is rarer, is controversial. We investigated the risk for SCCC and other eye cancers in the updated U.S. HIV/AIDS Cancer Match Registry Study. We calculated standardized incidence ratios (SIRs) to estimate excess risk for SCCC, primary ocular lymphoma, ocular Kaposi sarcoma (KS) and other eye tumors among 491, 048 adults (aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 21 publications
(49 reference statements)
1
49
0
3
Order By: Relevance
“…The conjunctiva is the only site in equatorial Africans that is not protected from ultraviolet light by heavy pigmentation . A causal role of heavy ultraviolet light exposure in SCCC onset is strongly supported by the geographical distribution of the disease (IARC, 2007;Guech-Ongey et al, 2008), and by the preferential onset of the malignancy in the intra-palpebral zone that is the part of the conjunctiva most heavily exposed to ultraviolet light . It can probably be assumed that all Ugandans are heavily exposed to ultraviolet light and it is therefore not surprising that no clear association was observed between outdoor occupation and SCCC risk in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conjunctiva is the only site in equatorial Africans that is not protected from ultraviolet light by heavy pigmentation . A causal role of heavy ultraviolet light exposure in SCCC onset is strongly supported by the geographical distribution of the disease (IARC, 2007;Guech-Ongey et al, 2008), and by the preferential onset of the malignancy in the intra-palpebral zone that is the part of the conjunctiva most heavily exposed to ultraviolet light . It can probably be assumed that all Ugandans are heavily exposed to ultraviolet light and it is therefore not surprising that no clear association was observed between outdoor occupation and SCCC risk in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The spread of human immunodeficiency virus (HIV) infection has been implicated in the rise of SCCC incidence both in Africa (Ateenyi-Agaba, 1995;Newton et al, 2001;Waddell et al, 2006) and the United States (Guech-Ongey et al, 2008), with an approximately 10-fold increased risk in individuals with HIV/AIDS. Mucosal human papillomavirus (HPV) types were initially suspected to have a role in SCCC onset because of their importance in the aetiology of carcinomas of the anogenital tract and oropharynx (IARC, 2007).…”
mentioning
confidence: 99%
“…No entanto é independente da forma de aquisição de VIH, valor de células CD4, ou tempo de evolução da infecção por VIH subjacente. 34 Neste caso, tratava--se de uma doente de raça negra, com infecção por VIH-2 conhecida com três anos de evolução, já muito imunodeprimida (CD4 99 células/ mm…”
Section: Discussionunclassified
“…47 OSSN is often referred to as immune-associated (mediated by diminished immune surveillance), as the risk of developing this disease is increased by 12-fold in HIV-infected individuals 48 and by 20-fold in liver-transplant patients. 49 Conjunctival SCC represents the most severe form of OSSN, causing ocular morbidity and if left untreated can result in mortality.…”
Section: Pterygia: Characteristics and Pathogenic Mechanismsmentioning
confidence: 99%
“…This is relevant particularly in regions where HIV is endemic (eg, Sub-Saharan Africa), as it has been shown that HIV infection increases the risk of developing conjunctival tumors by greater than 10-fold. 48 38 Despite this, at least three independent studies observed HPV-16 in their pterygium specimens. 29,35,36 Concurrent disease: pterygia and OSSN Pterygia have been referred to as benign tumors due to their local invasiveness and propensity to recur but not to metastasize.…”
Section: Pterygia: Characteristics and Pathogenic Mechanismsmentioning
confidence: 99%